2019
DOI: 10.1007/s00213-019-05325-w
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling reveals contrasting effects on reinforcement learning and cognitive flexibility in stimulant use disorder and obsessive-compulsive disorder: remediating effects of dopaminergic D2/3 receptor agents

Abstract: RationaleDisorders of compulsivity such as stimulant use disorder (SUD) and obsessive-compulsive disorder (OCD) are characterised by deficits in behavioural flexibility, some of which have been captured using probabilistic reversal learning (PRL) paradigms.ObjectivesThis study used computational modelling to characterise the reinforcement learning processes underlying patterns of PRL behaviour observed in SUD and OCD and to show how the dopamine D2/3 receptor agonist pramipexole and the D2/3 antagonist amisulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
136
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(174 citation statements)
references
References 81 publications
35
136
3
Order By: Relevance
“…Patients showed greater difficulties in adjusting their behavior following a rule change compared with HC. This finding is in line with earlier studies suggesting similar deficits in patients suffering from amphetamine (24,27) and cocaine (42) dependence from the United Kingdom. Using a combination of a "Go/No-Go" task with reversal learning, a study has shown maladaptive choices among cocaine and alcoholdependent patients when contingency change.…”
Section: Discussionsupporting
confidence: 93%
“…Patients showed greater difficulties in adjusting their behavior following a rule change compared with HC. This finding is in line with earlier studies suggesting similar deficits in patients suffering from amphetamine (24,27) and cocaine (42) dependence from the United Kingdom. Using a combination of a "Go/No-Go" task with reversal learning, a study has shown maladaptive choices among cocaine and alcoholdependent patients when contingency change.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that lower action precision was associated with fewer wins, and a greater number of shifts to a new choice after a win, suggest a failure of SUDs to settle on a behavior strategy despite sufficient evidence. This appears consistent with previous work suggesting that substance users are less likely than HCs to stick to successful decision strategies (Kanen et al, 2019;Myers et al, 2016). Future work will be necessary to better understand the possible bases of this difference (e.g., underconfidence, distractibility, reduced awareness, etc.).…”
Section: Discussionsupporting
confidence: 88%
“…Both opioid and stimulant (cocaine and/or amphetamine) users are less likely than HCs to stick to successful decision strategies and instead: (a) choose to switch responses even when a previous response has been rewarding (Myers et al, 2016); or (b) perseverate on responses independent of outcomes (Kanen et al, 2019). Similar difficulties in flexibly adjusting behavior following punishments have also been reported in other stimulant user samples ((Ersche et al, 2016;Ersche et al, 2011); but see (Kanen et al, 2019)). In contrast, stimulant users appear to exhibit heightened sensitivity to monetary reward (Ahn et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…A recent study showed changes in positive and negative feedback learning, as well as in response persistence (stickiness), in people with stimulant abuse disorder and obsessivecompulsive disorder (Kanen et al 2019), two psychopathologies in which the human PFC has been implicated (Bechara and Van Der Linden 2005;Volkow and Morales 2015). This may provide interesting clinical relevance to our findings, especially since these same authors provided a potential drug target (the dopamine D 2/3 receptor) for modulating these components of learning and decision-making in humans (Kanen et al 2019). In addition, the subregion-specific involvement of the mOFC and PrL in stickiness may be of special clinical importance, given the suggested involvement of maladaptive response persistence-irrespective of outcome-in addictive behaviors (Everitt and Robbins 2016).…”
Section: Discussionmentioning
confidence: 99%